Concept, Models and Methods of Sustainability in Croatian Companies - Tihomir Opetuk; Hrvoje Cajner; Goran Đukić; Davor Kolar (Tehnički Vjesnik, 2019)
Due to high greenhouse gas GHG emissions which will have great negative impacts on the environment in the following decades we will be facing significant climate changes. Because of the before mentioned fact many standards, directives, concepts, methods and models dealing with sustainability have appeared. This paper presents the survey which has been carried out in Croatia business sector in view of current state and trends, barriers and drivers of sustainability. First part of the paper consists of overview of Life Cycle Assessment, Product Lifecycle Management, Product Life Cycle Management, Life Cycle Management and Green Supply Chain Management terms. Second part of the paper presents the survey which is carried out in Croatia business sector regarding current state and trends of sustainability. The results show how well the companies are familiarized with and implement standards, directives, concepts, methods and models connected with sustainability.